A comparison of the performance of selected conceptual models of the rainfall-runoff process in semi-arid catchments near Grahamstown - Roberts, Peter J T (Rhodes University, Faculty of Science, Department of Geography, 1979)
A comparison of the performance of selected conceptual models of the rainfall-runoff process forms the central theme of this study and the comparison was conducted with three major objectives in mind. The first objective was to develop a conceptual model that could be used by practising hydrologists for the refinement and extension of historical streamflow records. The major requirements of the model were that it should be simple in structure and easy to operate and yet be flexible in terms of complexity of structure and input requirements as well as producing output at a level of accuracy that is competitive with that of the more complex models presently available. A comparison of the performance of the required model with that of other models formed an integral part of the development process. The second objective of the comparative study was to contribute to current knowledge of the criteria used in the selection of a suitable model for a particular application. There are, at present, no reliable guidelines to assist the hydrologist in selecting a suitable model from the wide range of models available and a comparative study would indicate the merits of various forms of model structure. The third objective is associated with the problems that arise when no streamflow data are available for model calibration. One approach is to calibrate the model in a nearby gauged catchment that the hydrologist regards as being 'hydrologically similar' and transferring the model parameter values to the ungauged catchment. Little is known about the feasibility of this parameter transfer process or about the choice of a model for such an application. The third objective was to test the feasibility of the parameter transfer process and to make use of the comparison of model performance to determine the model characteristics that are most suitable for the purpose
Keywords: Runoff; Rainfall -- South Africa -- Grahamstown